POTENSI TEH BUNGA TELANG (Clitoria ternatea) SEBAGAI OBAT PENGENCER DAHAK HERBAL MELALUI UJI MUKOSITAS - Aisyah Denta Kusuma (Risenologi, 2019)
Asthma is a chronic inflammatory disorder in the respiratory tract that can occur in both childrenand adults who are susceptible to inflammation with symptoms of recurrent wheezing, shortness ofbreath, chest pressure, and coughing as a result of the limited air entering the lungs. The purpose ofthis study was to determine the potential content of butterfly pea tea (Clitoria ternatea) as analternative medication to loosening mucus for asthmatics. This study uses an experimental researchmethod, where in this study investigated the mucolytic activity of butterfly pea tea, conditions,conditions, or other things, which are then presented in the form of a research report. The data in thisstudy were obtained from the results of mucolytic test of butterfly pea tea steeping on cow mucus. Theresults of this study are butterfly pea tea solution having mucolytic activity potential at aconcentration of 30% ????????? so that regular consumption can potentially help thin the phlegm due to adecrease in mucous flow rate after the addition of butterfly pea tea solution and there are similaritiesbetween cow mucus and human sputum.